2022
DOI: 10.1088/1741-4326/ac7888
|View full text |Cite
|
Sign up to set email alerts
|

Causal impact of tearing mode on zonal flows and local turbulence in the edge of HL-2A plasmas

Abstract: Direct causality analysis of the multi-scale interactions among macro-scale tearing mode (TM), meso-scale geodesic acoustic mode (GAM) and small-scale turbulence in the edge plasma of the HL-2A tokamak utilizing transfer entropy method is reported. Experimental results have demonstrated that the (m/n)=(2/1) (with m and n being the poloidal and toroidal mode numbers, respectively) TM modulates the turbulence with the frequency range of f=50-150 kHz and the GAM mainly modulates that with higher frequencies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In addition, experiments on the HL-2A tokamak have shown that the modulation effect of the MI on turbulence is limited to the inner region of the MI and there is a MI threshold for modulating the turbulence around w ∼ 4 cm [22], which is consistent with Fitzpatrick's theoretical predictions [23]. Most recently, the multi-scale interactions among macroscale TM, meso-scale geodesic acoustic mode (GAM) and small-scale turbulence are carried out in the edge plasma of the HL-2A tokamak using the causality analysis method and the effect of the MI width on the nonlinear coupling among turbulence, GAM and TMs is also reported [24,25].…”
Section: Introductionsupporting
confidence: 83%
“…In addition, experiments on the HL-2A tokamak have shown that the modulation effect of the MI on turbulence is limited to the inner region of the MI and there is a MI threshold for modulating the turbulence around w ∼ 4 cm [22], which is consistent with Fitzpatrick's theoretical predictions [23]. Most recently, the multi-scale interactions among macroscale TM, meso-scale geodesic acoustic mode (GAM) and small-scale turbulence are carried out in the edge plasma of the HL-2A tokamak using the causality analysis method and the effect of the MI width on the nonlinear coupling among turbulence, GAM and TMs is also reported [24,25].…”
Section: Introductionsupporting
confidence: 83%
“…Jingchun Li presented the experimental observation of the nonlinear interactions among turbulence, geodesic acoustic mode, and tearing mode in HL-2A edge plasmas. It is found that the nonlinear interaction between GAM and background turbulence decreases with the magnetic island width, while the interaction between the magnetic island and the density perturbation-associated turbulence increases [19]. A special observation is that magnetic island (MI) can significantly reduce turbulence levels, with a non-monotonic dependence of the suppression effect on MI width.…”
Section: Micro-turbulence and Transportmentioning
confidence: 98%
“…Jianqiang Xu et al investigated the characteristics of geodesic acoustic mode (GAM) and its causal impact on turbulent transport in deuterium (D) and hydrogen (H) dominated ohmic plasmas in the edge region of HL-2A tokamak utilizing the direct causality analysis method [19]. It is shown that the nonlinear coupling between GAM and ambient turbulence as well as the information transfer from the radial electric field fluctuation of GAM to the particle flux and turbulence energy is also shown to be larger in the deuterium regime in comparison with hydrogen, implying that the regulation of turbulent transport by GAM ZF in D plasma is stronger than that in H isotope.…”
Section: Micro-turbulence and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further investigate the modulation relationship between QCMs and turbulence, the envelope analysis [46] is used to identify interaction between the QCMs and AT. The envelope based on the analytic signal approach consists of a real signal of finite energy which is Fourier transformable and band-limited and the Hilbert transform of the original real signal.…”
Section: Impact Of Qcms On Pedestal Turbulencementioning
confidence: 99%